Granulin-Epithelin Precursor Is an Oncofetal Protein Defining Hepatic Cancer Stem Cells - Cheung, Phyllis Fung Yi (Public Library of Science, 2011)
BACKGROUND AND AIMS: Increasing evidence has suggested that hepatocellular carcinoma (HCC) might originate from a distinct subpopulation called cancer stem cells (CSCs), which are responsible for the limited efficacy of conventional therapies. We have previously demonstrated that granulin-epithelin precursor (GEP), a pluripotent growth factor, is upregulated in HCC but not in the adjacent non-tumor, and that GEP is a potential therapeutic target for HCC. Here, we characterized its expression pattern and stem cell properties in fetal and cancerous livers. METHODS: Protein expression of GEP in fetal and adult livers was examined in human and mouse models by immunohistochemical staining and flow cytometry. Liver cancer cell lines, isolated based on their GEP and/or ATP-dependent binding cassette (ABC) drug transporter ABCB5 expression, were evaluated for hepatic CSC properties in terms of colony formation, chemoresistance and tumorigenicity. RESULTS: We demonstrated that GEP was a hepatic oncofetal protein that expressed in the fetal livers, but not in the normal adult livers. Importantly, GEP+ fetal liver cells co-expressed the embryonic stem (ES) cell-related signaling molecules including β-catenin, Oct4, Nanog, Sox2 and DLK1, and also hepatic CSC-markers CD133, EpCAM and ABCB5. Phenotypic characterization in HCC clinical specimens and cell lines revealed that GEP+ cancer cells co-expressed these stem cell markers similarly as the GEP+ fetal liver cells. Furthermore, GEP was shown to regulate the expression of ES cell-related signaling molecules β-catenin, Oct4, Nanog, and Sox2. Isolated GEP(high) cancer cells showed enhanced colony formation ability and chemoresistance when compared with the GEP(low) counterparts. Co-expression of GEP and ABCB5 better defined the CSC populations with enhanced tumorigenic ability in immunocompromised mice. CONCLUSIONS: Our findings demonstrate that GEP is a hepatic oncofetal protein regulating ES cell-related signaling molecules. Co-expression of GEP and ABCB5 further enriches a subpopulation with enhanced CSC properties. The current data provide new insight into the therapeutic strategy.